ACTIVE POWER LOSS REDUCTION BY ENRICHED BAT ALGORITHM - Kanagasabai, Lenin (International Journal of Advances in Applied Sciences, 2021)
In this work Enriched Bat Algorithm (EBA) is projected to solve optimal reactive power problem. Bat algorithm based on swarm intelligence and stimulated from the echolocation behavior of bats. In this projected algorithm the directional attribute of echolocation is applied. Progression of bats is directed by superior bats, local schedule are advanced by calculating the step sizes. Pulse emission and loudness are customized to augment the performance of the algorithm. In the Enriched Bat Algorithm (EBA) in the region of two bats when the food is definite then the present bat shift to a direction at the neighbouring neighbourhood of the two bats where the food is believed to be ample. When it is not possible then it moves toward the most excellent bat. Proposed Enriched Bat Algorithm (EBA) has been tested in standard IEEE 14, 30, 57,118,300 bus test systems and simulation results show the projected algorithm reduced the real power loss comprehensively.